Calculati:
(x²+x+1)² -(x²+x)²
Răspunsuri la întrebare
Răspuns de
0
(x²+x+1)² -(x²+x)² =
(x²+x+1)² -(x²+x)² = 1
*poza e mai corecta *
(x²+x+1)² -(x²+x)² = 1
*poza e mai corecta *
Anexe:
Răspuns de
0
E(x) = (x² + x+ 1 +x² +x)( x² +x +1 - x² - x) = (2x² + 2x +1)·1 = 2x² + 2x +1
Alte întrebări interesante
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă